6 Answers

b^2A(a)(c)
b= 3
a= 1
c= 7
(3)^2  4 (1)(7)
9+28
=37
sqrt(b^2  4(a)(c))=sqrt(37)
X= b±sqrt(b^2  4(a)(c))

2a
X= 3±sqrt(37)

2
X=3+sqrt(37)

2
X=3sqrt(37)

2

x2  3x  7 = 0
(x  3/2)^2  37/4 = 0
Solutions:
x = (3  sqrt37)/2
x = (3 + sqrt37)/2

when Ax^2 + Bx + C = 0, then x = (B +/ Sqrt(B^2  4AC)) / 2A
For your equation, A = 1, B = 3, and C = 7
x = (3 +/ Sqrt((3)^2  4(1)(7))) / (2(1))
x = (3 +/ Sqrt(9 +28)) / 2
x = (3 +/ Sqrt(37)) / 2

I assume it's x^2  3x  7 = 0
Use quadratic formula [b + sqrt (b^2  4ac)]/2a
=((3) + sqrt ((3)^2  4(1)(7))) / 2(1)
= (9 + sqrt 37)/2 OR (9  sqrt 37)/2
= (9 + 6.083)/2 OR (9  6.083)/2

x1 = 3/2 + (1/2)*sqrt(37)
x2 = 3/2  (1/2)*sqrt(37)

x = [  b Â± â ( b Â²  4 a c ) ] / 2 a
x = [ 3 Â± â ( 9 + 28 ) ] / 2
x = [ 3 Â± â 37 ] / 2